Cultural Identity Through the Background Design of Three Animated Advertisements: The Perceptions of Z Generation - Arum Wulandari; Riksa Belasunda; Syarip Hidayat (Gondang: Jurnal Seni dan Budaya, 2026)
Background design in animated advertising is often treated as a secondary visual element, while most studies focus on character design and narrative. This study examines how background design in three Indonesian animated advertisements Sasa, Khong Guan, and Pocari Sweat functions as a representation of culture and how Generation Z audiences interpret the cultural meanings embedded within those backgrounds. Using a qualitative descriptive approach, the research applies Kurtz’s (2020) background art framework, including form, color, perspective, shadow and light, texture, art style, image placement, and narrative function. Cultural representation is analyzed through Koentjaraningrat’s concepts of ideas, activities, and artifacts, while audience reception is examined using Stuart Hall’s encoding–decoding theory through semi-structured interviews with 28 Generation Z informants aged 18–27. The findings show that each advertisement uses distinct visual strategies to construct representations of Indonesian cultural identity. Warm and cool color palettes function as cultural signifiers, perspective shapes the perception of space, and anime-inspired visual styles make local cultural content more globally accessible and commercially appealing. Among the 28 informants, 22 occupied the Dominant position, recognizing the cultural environments as familiar and emotionally resonant. Four informants occupied the Negotiated position, acknowledging tensions between anime aesthetics and Indonesian visual specificity, while two occupied the Oppositional position, criticizing the simplification and homogenization of regional cultural representation. This study demonstrates that animated advertisement backgrounds function not merely as decorative settings, but as culturally meaningful visual spaces that influence audience perception and cultural recognition among Generation Z.